A bioinspired Janus polyurethane membrane for potential periodontal tissue regeneration. Issue 14 (6th January 2022) - He, Yushui; Wang, Xiao; He, Yuanyuan; Zhao, Xin; Lin, Jingjing; Feng, Yuan; Chen, Jie; Luo, Feng; Li, Zhen; Li, Jiehua; Tan, Hong
Abstract : Here, we developed a bioinspired degradable polyurethane membrane with Janus surface morphology and function by integrating the bioactive dopamine (DA) and the antibacterial Gemini quaternary ammonium salt (QAS). Abstract : Guided tissue regeneration (GTR) is the main therapeutic method for periodontal tissue regeneration. The key to the GTR strategy is the membrane which can assist the reconstruction of bone tissue in the periodontal defect and prevent the migration of epithelium and fibroblasts to the defect. However, the existing periodontal membrane cannot effectively promote periodontal tissue regeneration due to the limited bioactivity and physicochemical function. Here, we developed a bioinspired degradable polyurethane membrane with Janus surface morphology by integrating bioactive dopamine (DA) and an antibacterial Gemini quaternary ammonium salt (QAS). The Janus surface of the membrane is fabricated through spontaneous microphase separation, resulting from the different migration of functional segments between the air-contact upper surface with enriched antibacterial QAS and the substrate-contact bottom with enriched bioactive DA. The smooth surface of the upper membrane used to face the soft tissues can reduce cell adhesion to suppress the migration of fibroblasts, while the rough surface with a topological micro-pit structure of the bottom side facing the bone has excellent function of autonomic mineralization and cell adhesion to promote bone tissue reconstruction. In addition, the membrane containing the antibacterial QAS shows excellent antibacterial effect on common oral pathogens, such as S. aureus and S. mutans . Moreover, the specific dopamine group also endows the membrane with excellent antioxidant efficiency. In vivo research shows that this Janus polyurethane membrane can effectively promote periodontal tissue regeneration in a rat periodontal defect model. Combined with its excellent mechanical properties and biocompatibility, the polyurethane membrane is a promising material for potential periodontal tissue regeneration.